A low cost validation method of finite element analysis on a thin walled vertical pressure vessels - Juan, Pratama; Deni Fajar, Fitriyana; Rusiyanto, .; Siregar, J. P.; Wahyu, Caesarendra (IOP Publishing, 2020)
Pressure vessel is a container that has been used to contain a pressurized fluids, either oil, gas, or other chemical fluids. It is widely used for the oil, gas and other chemical based industries. Nowadays, finite element analysis is commonly used to reduce the high cost of testing a pressure vessel before manufacturing process. However, further validation is needed to ensure the results of the simulation and safety of the pressure vessels. In this study, theory of distortion energy is used as the tools of validation based on materials properties and behavior. And finally to ascertain wether the pressure vessel is possible for production or a refinement for safety is needed. The results of the study shown that theory of distortion energy can be used as validation tool for finite element analysis on a pressure vessels, however it cannot ensure the safety. Therefore other validation methods are needed to ascertain the safety of the pressure vessel discussed in this report. The cost analysis shown that failure theory combined with other calculation methods can save costs in pressure vessel testing, although some fairly expensive tests cannot be avoided.